Bureaucracy and bureaucratization as a social phenomenon - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2020)
The article emphasizes that the bureaucracy is a special social group that has specific essential and mandatory features, due to which it plays an important role in the system of management of society. It is proved that the phenomenon of bureaucratization of not only management, but also all spheres of society, as a rule, is associated with the exit of functions of the bureaucracy beyond the limits of applicability of its essential structure and principles of activity. This, in turn, is due to the crisis of the socio-economic system of society and, consequently, of the authority, which expands the opportunities and claims of the bureaucracy in the management of the social system.
Keywords: bureaucracy; bureaucratization; management; social group; debureaucratization; dysfunction of bureaucracy